Malic enzyme, malate dehydrogenase, fumarate reductase and succinate dehydrogenase in the larvae of Taenia crassiceps (Zeder, 1800) - Zenka, J; Prokopic, J (Folia parasitologica, 1987)
Malate dehydrogenase, malic enzyme, succinate dehydrogenase, and fumarate reductase activities have been studied in the cytoplasm and mitochondria of Taenia crassiceps larvae. The results show that these larvae contain enzymes for anaerobic acquisition of energy with terminal fumarate reductase, but some facts, as the high ratio of succinate dehydrogenase activity to fumarate reductase activity and the low proportion of fumarate reductase in the whole NADH oxidase activity in mitochondria, suggest that aerobic processes are also involved in the energy acquisition in this parasite.
Keywords: Aerobiosis; Animals; mitochondrie; Cytoplasm; malátdehydrogenasa; aerobióza; zvířata; oxidoreduktasy působící na CH-CH vazby; Taenia; Succinate Dehydrogenase; Mitochondria; cytoplazma; Malate Dehydrogenase; sukcinátdehydrogenasa; Oxidoreductases Acting on CH-CH Group Donors; oxidoreduktasy; Oxidoreductases